Perancangan Instalasi Pengolahan Air Limbah (IPAL) untuk Pemukiman Padat Penduduk - Aldi Fadli Mohammad; Dipa Ryanda Pratama; I Putu Chrisjayadi Setia Putra; Muhammad Fairuz Suryo Prayogo; Rama Apriyono (International Forum of Researchers and Lecturers, 2026)
The increase in population and domestic activities in residential areas has led to a growing volume of domestic wastewater, which has the potential to pollute the environment if not properly treated. This study aims to design an effective, economical, and environmentally friendly community-scale Wastewater Treatment Plant (WWTP) to reduce pollutant concentrations before wastewater is discharged into receiving water bodies. The main parameters analyzed include Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), pH, and oil and grease. The research method consisted of field surveys, wastewater flow rate calculations, domestic wastewater characterization, and the design of treatment units comprising an equalization tank, sedimentation tank, anaerobic-aerobic biofilter, and chlorination tank. The design results indicate that the proposed WWTP is capable of reducing BOD by up to 85%, COD by 80%, and TSS by 90%, thereby complying with the domestic wastewater quality standards stipulated in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 68 of 2016. The proposed WWTP system is expected to provide a sustainable solution for domestic wastewater management in densely populated residential areas.